Managing climatic risks in rice–wheat cropping system for enhanced productivity in middle Gangetic plains of India - Jha, Ratnesh Kumar; Sattar, Abdus; Singh, Anil Kumar; Kundu, Madhu Sudan; Tiwari, Ravindra Kumar; Singh, Abhay Kumar; Singh, Arbind Kumar; Das, Sudhir; Pal, Ram; Kushwah, Sunita; Kumari, Anuradha Ranjan; Meena, Motilal; et al. (Frontiers in Sustainable Food Systems, 2023)
Rice followed by wheat is the dominant cropping system in the middle Indo-Gangetic plains (IGP). Lower productivity (4.8 t ha -1 ) of this cropping system in Bihar, compared to national average (6.8 t ha -1 ) due to several climate and production related issues is a matter of concern for the farmers and the policy makers. Keeping all this in view, an experiment with rice-wheat cropping system was carried out during 2020-21 and 2021-22 in 17 adopted villages of 13 districts of Bihar under the Project -Climate Resilient Agriculture Programme (CRAP)‖ to evaluate the feasibility of early transplanting of rice in the month of June with the aim of achieving higher system productivity by early harvesting of rice and subsequent timely sowing of wheat before 15 November with the provision of assured irrigation. In this study, the concept of an innovative community irrigation approach and single phase 3 hp submersible pump were employed. Long duration rice variety (150 days) Rajendra Mahsuri-1 was sown during 20-25 May in the nursery and transplanted through puddling operation during 15-20 June in 17 locations. Under delayed conditions, the nursery sowing and transplanting window were 10-15 June and 10-15 July, respectively. Timely sown rice grown with the provision of community irrigation system achieved the grain yield of 5.2 t ha -1 and 85.8 % higher water productivity, compared to late sown crop. Following the harvest of rice, HD-2967 variety of wheat was planted in the first fortnight of November and harvested in the first week of April, yielding 4.9 t ha -1 with the application of 2-3 irrigations based on soil type and evaporative demand. Timely harvesting of wheat facilitated farmers of the region to take an additional crop of summer green gram. With assured irrigation system and shifting planting dates and thereby managing climatic risks, the overall productivity of the rice-wheat cropping system was achieved to the tune of 10.1 t ha -1 with the cropping intensity of 300 % for better adaptation and sustainable production.